Leakage Current Assessment Using Correlation Coefficient and Principal Component Analysis on The Eight-Month Naturally Coastal Contaminated Outdoor Porcelain Insulator - Waluyo, Waluyo; Pakpahan, Parouli M.; Suwarno, Suwarno; Djauhari, Maman A. (Jurnal Teknik Elektro, 2008)
This manuscript presents the experimental results of eight months naturally coastal contaminated outdoor porcelain insulator. The conducted experiments were leakage current and applied high voltage measurements, in the hermetically sealed chamber, where temperature, humidity, pressure and applied voltage could be adjusted and measured simultaneously. The leakage current waveforms were analyzed using FFT and the relation to other parameters were analyzed using correlation coefficient and principal component analysis. On high humidity, the leakage current waveforms tended to approach pure sinusoides, and the amplitudes tended to rise. Based on the correlation coefficient, the relative humidity influenced to leakage current amplitudes and phase angle as 0.60 and -0.68 respectively. Whereas, using PCA, the humidity close to power factor, and the phase angle close to THD and applied voltage. However, the phase angle opposites to the humidity. The extracted for 2 and 3 components are 74.5% and 85.3% respectively.